Optimalisasi Proses Pembelajaran melalui Penerapan Metode Pengajaran Interaktif di MTs Muslimat NU Palangka Raya - Fajariah Fajariah; Akhmad Ali Mirza (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Effective learning is the primary goal in education, but traditional teaching methods are often considered less engaging for students. This article analyzes the implementation of interactive teaching methods at MTs Muslimat NU Palangka Raya to enhance student participation and motivation. This research employs a descriptive qualitative approach with data collection techniques such as observation, interviews, and documentation. The results indicate that the interactive method successfully creates a more dynamic learning environment, with students being more active in group discussions and presentations. This method also improved students' understanding of the material and their social skills, such as communication and collaboration. Overall, the interactive teaching method proved effective in enhancing the quality of learning and can be applied to other educational institutions.